Reactivity of TCNE and TCNQ derivatives of quinonoid zwitterions with Cu(i). Issue 12 (18th February 2015) - Kauf, Thomas; Rosa, Vitor; Fliedel, Christophe; Pattacini, Roberto; Deibel, Naina; Avilés, Teresa; Sarkar, Biprajit; Braunstein, Pierre
Abstract : The reactions of TCNE- and TCNQ-functionalized zwitterionic benzoquinonemonoimines with a Cu(i )-BIAN complex have been investigated and found to follow a diversity of interesting patterns. Abstract : The reactions of TCNE- and TCNQ-functionalized (TCNE: tetracyanoethylene and TCNQ: 7, 7′, 8, 8′-tetracyanoquinodimethane) zwitterionic benzoquinonemonoimines with a Cu(i )-BIAN complex (BIAN = bis( o, o ′-bisisopropylphenyl)acenaphthenequinonediimine) have been investigated and found to follow a diversity of interesting patterns. The complexes [Cu(BIAN)(NCMe)(L2 )]BF4 (2 ) and [Cu(BIAN)(L2 )2 ]BF4 (4 ) were obtained by reacting [Cu(BIAN)(NCMe)2 ]BF4 (1 ) with one and two equivalents ofL2, respectively. Following similar procedures, the complexes [Cu(BIAN)(NCMe)(L3 )]BF4 (6 ) and [Cu(BIAN)(L3 )2 ]BF4 (7 ) were obtained by reaction of1 withL3 . The reaction of2 with 0.5 equiv. of 4, 4′-bipyridine afforded [Cu(BIAN)(L2 )2 (μ-4, 4′-bipyridine)](BF4 )2 (3 ). The complexes were characterized by multinuclear NMR, IR and UV-Vis spectroscopic techniques, mass spectrometry, cyclic voltammetry and elemental analysis. The molecular structures of complexes3 ·4CH2 Cl2 and4 ·CH2 Cl2 were determined by single crystal X-ray diffraction. An unexpected coordination polymer [Cu(L2 − )2 ]∞ (5 ) was also structurally characterized, which contains Cu(ii ) centres chelated by two N, O-bound ligands resulting from the monodeprotonation ofL2 .